Mathematics learning orientation: Mathematical creative thinking ability or creative disposition? - Ibrahim; Khalil, Ibrahim Alhussain; Prahmana, Rully Charitas Indra (Journal on Mathematics Education, 2024)
Mathematical creative thinking skill often becomes the orientation of mathematics learning, aiming to enhance students’ creativity in mathematics. Recognizing that creativity encompasses the capacity for thinking creatively and creativity disposition is essential. Building on this conceptual foundation, the primary objective of this study is to develop a comprehensive model illustrating the relationship between students' aptitude for mathematical creative thinking and their creative disposition. The research methodology employed in this study aligned with the framework of cause-and-effect analysis. The study cohort consisted of 36 students, carefully selected by a cluster random sampling technique. The research instruments included a mathematical creative thinking ability assessment and a creative disposition scale. The data was analyzed using the Non-Recursive Structural Equation Modeling. The results showed the reciprocal cause-and-effect dynamic between mathematical creative thinking ability and creative disposition, exhibiting a mutually influential relationship with determination coefficients of 21.83% and 21.05%. This shows that mathematical creative thinking ability is better at explaining mathematical creative disposition than mathematical creative disposition explaining mathematical creative thinking ability, with a relatively small difference (0.78%). This study also concluded that an optimal approach to mathematics pedagogy entails a balanced and simultaneous focus on nurturing mathematical creative thinking ability and disposition.